(untitled) (Sustainability in Debate, 2019)
This study presents a discussion about the perception of the residents of Crixás, Brazil, regarding the degradation process of the Vermelho River. We examined the responses from 28 residents before and after they witnessed the induction of the mining company Serra Grande S/A. The research is qualitative and has an interpretative character. Further, we performed bibliographical and documentary research as well as fieldwork and had residents produce mental maps. The mental maps made it possible to apprehend, through written and pictorial language, their individual experiences and relationship with the river. The interpretation of the results indicated that for these participants, mining is one of the primary causes of the river degradation process; however, it also shows that other factors, such as sewage and garbage dumped into the river and removal of ciliary forest, contribute to the intensification of degradation, decline in biodiversity, and health problems in the population.